Claiming the Union : citizenship in the post-Civil War South - Lee, Susanna Michele, 1975-; Cambridge eBooks (Cambridge : Cambridge University Press, 2014)
This book examines Southerners' claims to loyal citizenship in the reunited nation after the American Civil War. Southerners - male and female; elite and non-elite; white, black, and American Indian - disagreed with the federal government over the obligations citizens owed to their nation and the obligations the nation owed to its citizens. Susanna Michele Lee explores these clashes through the operations of the Southern Claims Commission, a federal body that rewarded compensation for wartime losses to Southerners who proved that they had been loyal citizens of the Union. Lee argues that Southerners forced the federal government to consider how white men who had not been soldiers and voters, and women and racial minorities who had not been allowed to serve in those capacities, could also qualify as loyal citizens. Postwar considerations of the former Confederacy potentially demanded a reconceptualization of citizenship that replaced exclusions by race and gender with inclusions according to loyalty.
"We have fought the first skirmish": loyalty and citizenship -- Men's Union: fixing the standard of a Union man -- Women's Union: reckoning with the female Union man -- Former slaves' Union: bestowing charity or rewarding loyalty -- The colored Union: being all things to all men.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: United States. -- Commissioners of Claims; Confiscations -- Confederate States of America; Unionists (United States Civil War) -- Reparations -- Southern States; African Americans -- Reparations -- Southern States; Women -- Reparations -- Southern States; Citizenship -- United States -- History -- 19th century; Compensation (Law) -- United States; United States -- History -- Civil War, 1861-1865 -- Claims; United States -- History -- Civil War, 1861-1865 -- Confiscations and contributions; United States -- History -- Civil War, 1861-1865 -- Moral and ethical aspects; Electronic books